Splanchnic vein thrombosis-related mortality in the Veneto region (Italy), 2008–2019: Retrospective analysis of epidemiological data. Issue 209 (January 2022) - Turatti, Giacomo; Fedeli, Ugo; Valerio, Luca; Klok, Frederikus A.; Cohen, Alexander T.; Hunt, Beverley J.; Simioni, Paolo; Middeldorp, Saskia; Ageno, Walter; Kucher, Nils; Konstantinides, Stavros V.; Schievano, Elena; et al.
Abstract: Background: Splanchnic vein thrombosis (SVT) is an uncommon manifestation of venous thromboembolism. Epidemiological data on SVT-related mortality rate is not available to date. Methods: We investigated time trends in SVT-related mortality rate, 2008–2019, in Veneto, an Italian high-income region of approximatively 5, 000, 000 inhabitants. SVT-related deaths were identified by the following ICD-10 codes: I81 (portal vein thrombosis), K75.1 (phlebitis of portal vein), K76.3 (liver infarction), K76.5 (hepatic veno-occlusive disease) or I82.0 (Budd-Chiari syndrome). Results: During the study period, a total of 557, 932 deaths were recorded. SVT was reported in 823 cases; 776 (94%) consisted of portal vein thrombosis. The age-standardized SVT-related mortality rate varied from 1.47 (year 2008) to 1.52 (year 2019) per 100, 000 person-years. An increase in the cause-specific annual mortality rate was observed in women (0.56 in 2008 to 1.04 per 100, 000 person-years in 2019; average annual percent change +5.7%, 95%CI +3.1; +8.3%). In men, the cause-specific mortality rate moved from 2.53 in 2008 to 2.03 per 100, 000 person-years in 2019 (average annual percent change −1.2%, 95%CI -4.0; +1.6%). After conditioning for age and sex, the odds of having a concomitant liver disease were higher for SVT-related deaths (OR 31.6; 95%CI 17.1–37.0) compared with non-SVT-related deaths. This also applies to gastrointestinal cancers (OR 1.28; 95%CI 1.07–1.55), although to a lesser extent. Conclusions: We report first epidemiological estimates of SVT-related mortality in a Western country. These values will serve as a reference to weight novel potential factors associated with SVT-related death and interpret them from an epidemiological perspective. Highlights: This is the first epidemiological study on splanchnic vein thrombosis (SVT)-related mortality SVT-related mortality was twice as high in men compared to women. We observed a strong association for both sexes between SVT and liver diseases. In women, the trend in SVT-related mortality rate was toward increase between 2008 and 2019. Bleedings were two-time higher among patients with SVT-related deaths.